We have to express the given radical expression in simplest radical form:

\(\displaystyle\sqrt[3]{56}\)

We know the laws of exponents,

\(\displaystyle\sqrt[m]{a}={a}^{{{\frac{{{1}}}{{{m}}}}}}\)

\(\displaystyle{\left({a}^{{m}}\right)}^{{n}}={a}^{{{m}\times{n}}}\)

\(\displaystyle{\left({a}{b}\right)}^{{m}}={a}^{{m}}{b}^{{m}}\)

Applying above laws for the given expression, we get

\(\displaystyle\sqrt[3]{56}={\left({56}\right)}^{{\frac{{{1}}}{{{3}}}}}\)

\(\displaystyle={\left({8}\times{7}\right)}^{{\frac{{{1}}}{{{3}}}}}\)

\(\displaystyle={\left({2}\times{2}\times{2}\times{7}\right)}^{{\frac{{{1}}}{{{3}}}}}\)

\(\displaystyle={\left({2}^{{3}}\times{7}\right)}^{{\frac{{{1}}}{{{3}}}}}\)

\(\displaystyle={\left({2}^{{3}}\right)}^{{\frac{{{1}}}{{{3}}}}}{\left({7}\right)}^{{\frac{{1}}{{3}}}}\)

\(\displaystyle={2}\sqrt[3]{7}\)

Hence, simplest form of the radical expression is \(\displaystyle={2}\sqrt[3]{7}\)